(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Observing changes in procalcitonin concentration in patients who respond and do not respond to antibiotic treatment. Subjects and methods: 50 patients were diagnosed with sepsis (positive blood culture) hospitalized at Le Van Thinh Hospital, Ho Chi Minh city, from November 2024 to October 2025. Study design cross-sectional prospective descriptive study. Procalcitonin concentration was measured using the DxI 800 analyzer. Results: The mean age of the patients was 58.08 years, with a female-to-male ratio were 1.7/1. The procalcitonin concentration at hospital admission was 19.48 ng/ml (median 3.73 ng/ml). Among the cases, 68% were Gram-negative and 32% were Gram-positive. The mean procalcitonin levels in the antibiotic-responsive group at 0 hours, 24 hours, 48 hours, 72 hours, and at 5-7 days after initiation of treatment were 15.29 ng/mL, 17.77 ng/mL, 8.31 ng/mL, 3.22 ng/mL, and 0.87 ng/mL, respectively; the differences across time points were statistically significant (p = 0.001). In the non-responsive group, the mean procalcitonin levels at 0 hours, 24 hours, 48 hours, and 72 hours were 38.57 ng/mL, 69.68 ng/mL, 22.27 ng/mL, and 17.04 ng/mL, respectively; the differences across time points were not statistically significant (p = 0.180). Conclusion: Procalcitonin levels decrease early in the first days in sepsis patients who respond to antibiotic treatment. In contrast, procalcitonin levels decrease minimally or remain unchanged in patients who do not respond to antibiotic treatment.